Lição: Algumas reflexões sobre agenciamento e atividade fora do sistema comercial. - Fletcher, Harrell (Revista Apotheke, 2022)
Harrell Fletcher received his BFA from the San Francisco Art Institute and his MFA from California College of the Arts. He studied organic farming at UCSC and went on to work on a variety of small Community Supported Agriculture farms, which impacted his work as an artist. Fletcher has produced a variety of socially engaged collaborative and interdisciplinary projects since the early 1990’s. His work has been shown at SFMOMA, the de Young Museum, the Berkeley Art Museum, the Wattis Institute, and Yerba Buena Center for the Arts in the San Francisco Bay Area, The Drawing Center, Socrates Sculpture Park, The Sculpture Center, The Wrong Gallery, Apex Art, and Smackmellon in NYC, DiverseWorks and Aurora Picture show in Houston, TX, PICA in Portland, OR, CoCA and The Seattle Art Museum in Seattle, WA, Signal in Malmo, Sweden, Domain de Kerguehennec in France, The Tate Modern in London, and the National Gallery of Victoria in Melbourne, Australia. He was a participant in the 2004 Whitney Biennial. Fletcher has work in the collections of MoMA, The Whitney Museum, The New Museum, SFMOMA, The Hammer Museum, The Berkeley Art Museum, The De Young Museum, and The FRAC Brittany, France. From 2002 to 2009 Fletcher co-produced Learning To Love You More, a participatory website with Miranda July. Fletcher is the 2005 recipient of the Alpert Award in Visual Arts. His exhibition The American War originated in 2005 at ArtPace in San Antonio, TX, and traveled to Solvent Space in Richmond, VA, White Columns in NYC, The Center For Advanced Visual Studies MIT in Boston, MA, PICA in Portland, OR, and LAXART in Los Angeles among other locations. Fletcher is an Associate Professor of Art and Social Practice at Portland State University in Portland, Oregon. Fonte: http://www.harrellfletcher.com/?page_id=37